A colocação dos pronomes átonos na escrita culta do domínio jornalístico e nos inquéritos do projeto NURC: uma análise contrastiva - Libia Mara Silva Saraiva (2008)
This paper is a comparative analysis of the placement of unstressed pronouns in two types of formal texts: those that have been produced in the actual journalistic mastery and those produced by NURC Project to check interference of the spoken language in the written language. It was also investigated the coincidence degree (or not) among the caught examples and the traditional grammar prescriptions to identify which linguistic reasons justify their occurrences. The obtained data indicated signs of disappearance of the tmesis and pointed to differences between the two investigated modalities of language (oral and written) attestingpreferences to proclisis in both kinds of samples, caused by vocabulary attraction. Moreover, the results confirmed the pressing need of a review in traditional grammars regarding pronoun placement, taking into account the current form of written Portuguese and to the teaching ofthe standard norm of the language in the Brazil as well.